Effect of Inorganic Fertilizer and VP3 Biofertilizer Applications in Legume on the Population of Indigenous Bacteria - Novi Arfarita; Tsuyoshi Imai; Cahyo Prayogo (AGRIVITA, Journal of Agricultural Science, 2023)
This current study is to examine the effects of inorganic fertilizers which are allegedly able to reduce the population of indigenous bacteria and the application of bacteria from VP3 biofertilizer on three test plants (legumes). In all treatments, the addition of inorganic fertilizer at a dose of 50% and 75% could significantly reduce population of soil bacteria on the 10th and 49th day observations. This also shows that the higher dose of NPK fertilizer also affects the bacteria from VP3 biofertilizer. However, treatment with 25–100% NPK fertilizers caused the decreasing of soil bacteria since the day of planting. In bean and long bean plants, the highest yields were shown at the combination of compost, VP3 biofertilizer and the addition of 75% NPK. Meanwhile, for mung bean, the highest yields were produced from the combination treatment of compost, VP3 and 50% and 75% NPK biofertilizers. However, the treatment of VP3 biological fertilizer with compost without the addition of NPK fertilizer on 3 legumes was able to give higher yields than the treatment of single NPK fertilizer.